Pengaruh Penambahan Pati Ganyong (Canna Edulis K.) Termodifikasi Secara Heat Moisture Treatment (HMT) Terhadap Karakteristik Bakso Ayam - Hafifa, Qoriatul; Sri Wiadnyani, Anak Agung Istri; Diah Puspawati, Gusti Ayu Kadek (Jurnal Ilmu dan Teknologi Pangan (ITEPA); Vol 12 No 4 (2023): Jurnal ITEPADO - 10.24843/itepa.2023.v12.i04.p01, 2023)
Chicken meatballs are commonly made of chicken meat and flour with various seasonings. This study aimed to determine the effect of heat-moisture treatment (HMT) modified canna starch addition on the characteristics of chicken meatballs and also to determine the right amount of heat-moisture treatment (HMT) modified starch addition to produce chicken meatballs with the best characteristics. A Completely Randomized Design (CRD) were used, with HMT addition treatment consisting of 6 types: P0: control (tapioca 25%), P1:5%, P2:10%, P3:15%, P4:20%, P5:25%. The treatment was repeated 3 times, so 15 experimental units were obtained. The obtained data were analyzed by analyzed of varian (ANOVA) on the SPSS program which was followed by Duncan’s Multiple Range Test (DMRT). The observed parameters in this study are water absorption content, elasticity level, water content, ash content, protein content, fat content, carbohydrate content, sensory test (hedonic and scoring), and resistant starch content. The result showed that the addition of HMT-modified canna starch had a significant effect on water absorption content, elasticity level, water content, protein content, fat content, carbohydrate content, color (hedonic and scoring), and resistant content. Chicken meatballs with the best characteristics were obtained from the addition of modified canna starch by heat moisture treatment (HMT) 25% with water absorption capacity of 33.82%, elasticity 7.57 N, moisture content 64.33%, ash content 0.79% , protein content 13.36%, fat content 5.24%, carbohydrate content 16.25%, and resistant starch content 3.00% as well as sensory assessment of color, namely dark ash and preferred, ordinary aroma, slightly chewy texture and preferred, ordinary taste and overall acceptance is preferred.